PENGARUH PEMBERIAN HORMON GIBBERELLIC ACID (GA3) TERHADAP PERTUMBUHAN TANAMAN CABAI RAWIT - Zilvy Na’imatur Rohmania (Program Studi Pendidikan Biologi, 2021)
Abstract: Cayenne pepper (Capsicum frutescens L.) is a type of shrub that has wood, branches, and grows upright. The content of nutrients in cayenne pepper includes calories, protein, fat, carbohydrates, minerals, vitamins, and medicinal substances such as capsaicin, bioflavonoids, and essential oils. The increase in the growth of chili plants is known because of the balanced coordination of auxins, cytokinins, and gibberellins in the plant growth system. One of the growth regulators that can be used to increase production in chili plants is gibberellin. This study aims to determine the effect of gibberellin on the growth of cayenne pepper with different treatments, namely treatment A (GA3 0 ppm), B (GA3 100 ppm), C (GA3 200 ppm), and D (GA3 300 ppm) with six times repeat. Parameters measured were plant height, leaf width, leaf length, and the number of fruits. The method used was a completely randomized design (CRD), based on each treatment the F table 5% (3.10) and 1% (4.94) tests were used with the results of F count plant height (18.8), leaf width (8, 9), leaf length (8,1) and the number of fruits (5,9). In this study, the best treatment is treatment C (GA3 200 ppm).